Energy Optimal Coverage Motion Trajectory Generation using a Fourth-order Motion Profile - Halinga, Mathias S. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Industrial machines are widely used in manufacturing sector to manufacture several products to meet customer demands. Most of these industries runs all the time throughout a day leading to high operating cost. To cut costs and satisfy customer demand for precise products, industrial machines’ motion generation is important in improving machine motion precision while using less energy. This study presents a coverage motion energy optimization which is generated by linear interpolation of each segment described by the fourth-order motion profile. The phase changes in the profile are attained with continuity of machine kinematic limits jerk, acceleration, and velocity, which are crucial to realize accurate motion. Genetic Algorithm is used to generate an optimal coverage motion using the convergence approach whereby the converged solution is selected as the final solution achieving minimum energy consumption. The simulation study is provided to illustrate the effectiveness of the proposed technique. The energy saving is about 9.27% when compared to unoptimized path. The approach can be utilized in several industrial machines employing coverage motion with the processes such as polishing, milling, laser cutting, and inspection